The phylogenetic analysis of the new emerging ALV-K revealing the co-prevailing of multiple clades in chickens and a proposal for the classification of ALV-K - Guo, Jinhan; Deng, Qiaomu; Zhu, Weiyu; Fu, Fumei; Liu, Linmin; Wei, Tianchao; Wei, Ping (Frontiers in Veterinary Science, 2023)
Subgroup K avian leukosis virus (ALV-K) is a new subgroup of avian leukosis virus (ALV) that was first defined in 2012 and has been become prevalent in Chinese native chickens in recent years. An in-depth analysis of the genetic diversity of ALV-K was performed in the study. By Blast analysis, the env gene and the sequences of the 25 ALV-K isolates we isolated were found to be closely related to the isolates from Guangdong, Hebei, Jiangsu, and Hubei provinces, China. Further eighty-nine sequences of the gp85 gene of ALV-K strains available were used in the phylogenetic and genetic distance analyses for the classification. ALV-K was divided into two second-order clades (Clades 1.1 and 1.2) and three third-order clades (Clades 1.2.1, 1.2.2, and 1.2.3), indicating that only two clades (1.1 and 1.2.3), which are prevalent in Japan, but also two new clades (1.2.1, 1.2.2), are co-prevalent in China. The representative strains of each clade were defined for the first time. Notably, Clade 1.2.2 was found to have a deletion of an amino acid residue in the gp85 gene, which was obviously different from Clades 1.1, 1.2.1, and 1.2.3. The proposed classification method will facilitate future studies of ALV-K epidemiology and the comparison of sequences obtained across the world. The first global comprehensive molecular epidemiological analysis was accomplished on the emerging ALV-K.